Popular education: an alternative for the development of human capacities in the resolution of socioenvironmental conflicts - Carol Peña-Palma; José Terán-Serna; Ángel Gil-Torres; Marly Tafur-Osorio (Íconos)
This article aims to disseminate the results of the first stage of the project “Popular environmental education for the strengthening of human capacities in the El Neme village”. The project seeks to facilitate the resolution of socio-environmental and local conflicts within the methodological framework provided by participative action research approaches. Using popular education theory as a point of departure, a popular environmental school is collaboratively built by the university and the local community. This proposal is an attempt to build an alternative method for the management and resolution of social-environmental conflicts and generate participative dynamics that can help the blossoming and strengthening of the human capabilities of the villagers. It also aims at assisting the local community into taking a leading role in building “a future with a future”. As a result of the construction of the school, the following advances are identified: 1. the idea of building the school appears as a result of the residents´ perceived need of developing and promoting new ideas that can help solve the socio-environmental conflicts that plague the community 2) By taking a supportive role, the university hopes to establish a more egalitarian relationship with the community. Finally, although after the first phase of the project has been completed, there are still pending socio-environmental conflicts within the community; the dwellers are now very much aware that they “will be left with no place to live in” if timely action is not taken.